Preserving Cultural Heritage and Fostering Community Engagement: A Case Study of Sustainable Tourism Development in Ciletuh Palabuhanratu UNESCO Global Geopark - Hermawati, Rina; Irawati, Ira; Munajat, MD Enjat; Saefullah, Kurniawan (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2024)
Community-Based Tourism (CBT) is a type of tourism that includes community participation as the main element in achieving sustainable tourism development goals. Community participation can be realized if a community has substantial social capital to move collectively to increase living standards. This research explores the community's cultural values in the UNESCO Ciletuh Palabuhanratu Global Geopark (CPUGG) area as the main element in forming community social capital. Using a qualitative case study type method, the author explains the dynamics of business actors in Ciletuh in developing their businesses through the concept of social capital, which includes social relationships, norms, values, and beliefs in society. The research results show Sundanese cultural values, such as (1) Sabilulungan; (2) Someah Hade Ka Semah; (3) Ngaruwat Alam; (4) Ngamumule Budaya; and (5) Spiritual values and beliefs. These cultural values are essential in forming social capital supporting tourism development in CPUGG. However, communities face various conflicts that can hinder tourism development